Controllable Swarming and Assembly of Micro/Nanomachines - Liu, Conghui (Micromachines (Basel), 2017)
Motion is a common phenomenon in biological processes. Major advances have been made in designing various self-propelled micromachines that harvest different types of energies into mechanical movement to achieve biomedicine and biological applications. Inspired by fascinating self-organization motion of natural creatures, the swarming or assembly of synthetic micro/nanomachines (often referred to micro/nanoswimmers, micro/nanorobots, micro/nanomachines, or micro/nanomotors), are able to mimic these amazing natural systems to help humanity accomplishing complex biological tasks. This review described the fuel induced methods (enzyme, hydrogen peroxide, hydrazine, et al.) and fuel-free induced approaches (electric, ultrasound, light, and magnetic) that led to control the assembly and swarming of synthetic micro/nanomachines. Such behavior is of fundamental importance in improving our understanding of self-assembly processes that are occurring on molecular to macroscopic length scales.